PCC CEMENT DEMAND FORECASTING USING SINGLE EXPONENTIAL SMOOTHING METHOD AT PT SEMEN TONASA - Atik Febriani; Muh Ikhwanul Ahkam Febriani; Gunawan Mohammad (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Employee productivity is a strategic factor in enhancing an organization's operational efficiency and competitiveness. However, human resource management in many companies remains suboptimal, particularly regarding the development of human capital quality that supports productivity. This study aims to analyze the impact of education, work experience, and job training as dimensions of human capital on the productivity of PT XYZ employees. Unlike previous studies that tended to examine human capital aspects in isolation or within specific organizational contexts, this research integrates these three dimensions into a single model to provide a more comprehensive understanding of the factors driving productivity within the study's scope. The selection of these three dimensions is grounded in Human Capital Theory, which views education as the foundation of knowledge, work experience as the accumulation of practical competence, and training as a mechanism for continuous competence development. A quantitative approach was employed, utilizing a survey of 150 respondents selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression in SPSS. The results indicate that education (β = 0.241; p < 0.05), work experience (β = 0.356; p < 0.05), and job training (β = 0.418; p < 0.05) all have a positive and significant effect on work productivity. Collectively, the three variables exert a significant influence, with an Adjusted R-squared value of 0.682. Job training emerged as the factor making the largest contribution. These findings underscore the importance of integrated human capital development strategies in boosting organizational productivity and competitiveness.